IMPACT OF AQUACULTURE ON EUTROPHICATION IN CHANGSHOU RESERVOIR - Zhang Sh.; Liu J.; Wei Sh.; Gao J.; Wang D.; Zhang K. (My University, 2006)
As a result of intensifying human activities around the Changshou Reservoir, water environmental quality has declined over the years. Water quality had been monitored from 1999 to 2002. The result indicated that the concentrations of total nitrogen (TN) and total phosphorus (TP) are high. The concentrations of phosphorus range from 0.037 mg/L to 0.444 mg/L, exceeding the critical value (0.02 mg/L) for eutrophication. The concentrations of total nitrogen and chlorophylla range from 0.70 mg/L to 4.18 mg/L and from 1.10 mg/m3 to 61.2 mg/m3, respectively. The eutrophication status of the water body was assessed using the method of integrated nutrition state index, which revealed that all sampling sites were eutrophicated from the year of 2001. About 69.6% of the annual total nitrogen input and 26% of the annual total phosphorus input originated from the upstreams. The contributions of nitrogen and phosphorus from precipitation to the water body are very small (0.9% and 0.3%, respectively) owing to their low contents (1.21 mg/L and 0.029 mg/L, respectively). Runoff is the secondarily important input source, which accounts for 19.0% of the total N input and 47.0% of the total P input, respectively. Attention should be paid to the aquaculture inputs, whose contributions account for 10.5% of the total N and 26.6% of the total phosphorus to the water body, respectively. Nutrient loads are estimated to be 118 gNm−2·a−1 and 8 gPm−2·a−1. About 69.4% of nitrogen and 79.7% of phosphorus input into the reservoir were retained in 2002.
Keywords: AQUACULTURE; EUTROPHICATION; CHANGSHOU RESERVOIR; NUTRITION STATUS